Behind the fencing mask: attentional and emotional processes of elite level fencers - Bracco, M.; Pete, E.; Bagot, P.; Bernier, M.; Fournier, J.; Doron, J.; Martinent, G. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction Fencing is a combat sport requiring a high attentional demand. According to Roi and Bianchedi (2008, p.474), fencers "must analyse and select the visual information provided by the opponent" in order to perform their own actions. Furthermore, as in any discipline, emotions are an integral part of the competitive experience, and the need for coping strategies is predominant in order to deal with stressful situations (Jones, 2003; Lazarus, 2000). This study aimed to identify attentional foci and coping strategies of elite fencers during bouts. Methods Twenty-two elite epee fencers (11 males and 11 females) from a senior national team took part in a simulated tournament. Retrospective video-recall interviews were held after their matches in order to ask fencers about their attentional foci and coping strategies. Inductive and deductive qualitative analyses were conducted on athletes` verbatims. Results Qualitative analysis of athlete`s verbatims revealed three categories of attentional foci: (a) cues (i.e. focus on oneself and focus on the environment), (b) strategy and tactics (e.g. having one or more strategies, automatic performance, absence of planning effort) and (c) extraneous attention. In order to manage their emotions, fencers used different types of coping strategies: (a) task-oriented strategies (e.g. concentration effort, seeking solutions) and (b) disengagement strategies (e.g. mental or physical disengagement). They also mentioned, in a lesser proportion (d) deliberate absence of regulation effort and (e) automatic regulation. Discussion Results highlighted the value of an ecological approach to explore athletes` cognitions. The results expand those of previous naturalistic studies, which showed that experts` attentional foci were diverse in content as in characteristics, and dynamic along the different performance phases. In line with previous research, athletes could also combine several coping strategies in order to manage their emotional state. To conclude, fencers called upon numerous attentional foci and coping strategies during points, breaks, and across the bout as a whole, providing insights on how these athletes deal with competitive situations.